The Duration of Breastfeeding and Its Association with Metabolic Syndrome among Obese Children - Renata Yakubov; Erez Nadir; Roni Stein; Adi Klein-Kremer (The Scientific World Journal)
Objective. The objective of this study was to evaluate whether duration of breastfeeding is associated with a lower prevalence of metabolic syndrome in obese children. Methods. A retrospective analysis of obese children aged 3 to 18 years followed at a pediatric outpatient clinic at a single center between the years 2008 and 2012. The children were divided according to their breastfeeding duration: no breastfeeding, a short period of breastfeeding, and a long term breastfeeding. Also, they were divided into metabolic and nonmetabolic syndrome groups, based on physical examination and laboratory tests. Results. Out of 4642 children who visited the clinic, 123 were obese and were included in the study. About half of them matched the metabolic syndrome criteria. There was no correlation between the prevalence of metabolic syndrome and the duration of breastfeeding. Hypertension, abnormal low levels of HDL, high levels of HbA1c, and high fasting triglyceride levels were very common in our study population, yet no statistical significance was noted among the different breastfeeding groups. Conclusion. In this study, breastfeeding was not associated with a reduced risk for metabolic syndrome, compared with formula feeding, in children who are obese.